PENGARUH KINERJA KEUANGAN TERHADAP RATE OF RETURN (ROR) PADA PERUSAHAAN PEMENANG AWARD TAHUN 2013-2015 - Apriyanti Apriyanti; Muhammad Agus Sudrajat (Universitas Muhammadiyah Malang, 2017)
This study aims to test empirically the financial performance measured through Return OnAssets (ROA), Return on Investment (ROI), Earning Per Share (EPS), Return On Equity (ROE),Operating Cash Flow (OCF), Net Profit Margin (NPM) and Economic Value Added (EVA) partially and simultaneously affect the Rate of Return (ROR). The population in this study are allaward winning companies namely Annual Report Award (ARA), Indonesian CSR Award (ICA),Indonesia Sustainability Reporting Awards (ISRA) year 2013-2015. The sampling techniqueused is purposive sampling, after passing through the screening process obtained 38 samples ofthe Company. The analize technique used is linear regression. The results showed that ROA hadsignificant negative effect; ROI, EPS, ROE, NPM have a significant positive effect; OCF has nosignificant negative effect; EVA doesn’t show any significant positive effect on ROR. Simultaneously ROA, ROI, EPS, ROE, OCF, NPM, EVA have significant positive effect to ROR.Keywords: EPS, EVA,NPM, OCF, ROR.